Influence of the EL NIÑO phenomenon on wave conditions in deep waters in front of the Peruvian coast - Ramos, Carmela (2020)
Wave Data in Deep water (outside wave generation zone at depth more than 500m) from 3 location in Perú were analyzed from 1979 to 2017 from NOAA reanalysis Data Base obtained with Wave Watch Simulation for global waves with 0.5°x0.5° spatial resolution. A time series was obtained to represent normal conditions and extreme event including El Niño and La Niña Phenomenon, thus extraordinary El Niño (EN) occurred in 1982-1983 and 1997-1998. Wave time series were calibrated with NOAA buoy data called 32012 from NDBC and satellite date obtained from GEOSAT, ENVISAT, JASON 1, ERS1, ERS2 y TOPEX/POSEIDON. Thus, a calibrated time series were obtained with an interval of 3 hours. Results shows that during EN the predominant significant wave height reached 1.5 to 2.5 m, and it represent an incremented around 1cm respect normal conditions, while wave period predominant range is around 13.5 to 15 seconds and it represent significant variations respect normal conditions, a similar case occurred with wave direction, during EN is most occurred waves from Northwest respect normal conditions.